2012
DOI: 10.12806/v11/i2/tf2
|View full text |Cite
|
Sign up to set email alerts
|

Leadership, Motivation, and Teamwork Behaviors of Principal Investigator’s in Interdisciplinary Teams: A Synthesis of Research

Abstract: Incoming first-year college students (N = 4,292) were surveyed regarding attitudes and beliefs about leadership. Students' opinions about their leadership ability were high and were related to having an outgoing personality, as well as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The results of this study in line with the results of research Elqadri (2015) showed that the motivation of work affect the discipline of work. In line with the results of research Rahimi (2015), Murcia (2008), and Adams (2012) which shows that the motivation of work has a significant effect on the discipline of work. Work discipline will increase if there is high employee motivation in performing daily tasks.…”
Section: Discussionsupporting
confidence: 87%
“…The results of this study in line with the results of research Elqadri (2015) showed that the motivation of work affect the discipline of work. In line with the results of research Rahimi (2015), Murcia (2008), and Adams (2012) which shows that the motivation of work has a significant effect on the discipline of work. Work discipline will increase if there is high employee motivation in performing daily tasks.…”
Section: Discussionsupporting
confidence: 87%
“…The achievements and reputations from at least 2013 to 2018, namely: (1) Leading trusted quality school from the 2015 global development foundation, (2) The best improvement vocational school from the image of Indonesia in 2015, (3) The best inspiring leader from Indonesia achievement center in 2015, (4) As the education and turoring program from the 2016 Indonesia awards center, (5) Reliable Indonesian educator from the Indonesia development service foundation in 2014, (6) The best education and educator from Indonesia achievement awards in 2017, (7) Indonesian award of education from the award of human achievement in 2016, (8) Special award for international Islamic school robotic olympiad in Malaysia in 2017, (9) National reference vocational school from the Directorate of PSMK Kemendikbud RI in 2017, (10) Launching microbus Suryawangsa by the Ministry of Education and Culture Republic of Indonesia in 2017, (11) 1st place LKTI at the national level in the 2016 Olympics, (12) 3rd place in Olympic de robotics at the national level of the Republic of Indonesia Ministry of Research and Technology 2016, (13) Champion 3 PTK at the national level of Olympic in 2016, (14) The gold medal of the international Islamic schoolrobotic olympiad was conceived in 2016, (15) Special award at the international robotic olympiad school in Bandung in 2016, ( 16) 2), it is explained that aspects of the principal's assessment on the basis and responsibilities of the principal schools as, 1) leaders, 2) managers, 3) Educators, 4) Administrators, 5) Entrepreneurs, 6) Work climate creators, 7) Supervisors. Allport, G.W.…”
Section: Introductionmentioning
confidence: 99%
“…Maximum productivity obtained by teamwork due to opinion and suggested interaction of members in an organization to completing tasks in accordance with compiled arrangement. Bruce and Ricketts stated "teamwork is extremely important among cross-disciplinary groups in order to produce effective and efficient work" [16]. Teamwork is a designed activity and accomplished by an organization and therefore cooperation of each element improves it.…”
Section: Introductionmentioning
confidence: 99%